Optimization of ligninolytic enzymes production from Aspergillus terreus SG-777 by solid state fermentation: Sahar Ghazi Imran1, Ghazi M.Aziz2 and Nada Sabah Razuqi3 - Imran, Sahar Ghazi (The Iraqi Journal of Veterinary Medicine, 2016)
The present study aimed at producing the ligninolytic enzymes extracts by growing single and co-cultures of an indigenous Aspergillus terreus SG-777 utilizing solid state fermentation (SSF) using lignocellulosic substrates. A further goal was to optimize the production condition of ligninolytic enzymes by selected fungal culture and lignocellulosic substrate. The production process was further improved by optimizing a number of physical parameters such as (substrate, incubation time, moisture level, inoculum size, pH, and temperature). By optimization of different parameters, the maximum specific activities of enzymes synthesized by Aspergillus terreus SG-777 were observed as 0.83 U/mg for manganese peroxidase (MnP), 18.03 U/mg for lignin peroxidase (LiP) and 0.91 U/mg for laccase, when using the banana stalks as substrate after 8 days incubation at рH 5.5 and 35°C temperature with 1×105 spore/ml ml inoculum size, 1:5 w/v moisture content, 20:1 C:N ratio (glucose and ammonium tartarate as carbon and nitrogen supplements), 1ml of 1mM MnSO4 as mediator, and 1ml of 1mM MgSO4.7H2O2.